-3t(t-1)=2t+6

Simple and best practice solution for -3t(t-1)=2t+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3t(t-1)=2t+6 equation:


Simplifying
-3t(t + -1) = 2t + 6

Reorder the terms:
-3t(-1 + t) = 2t + 6
(-1 * -3t + t * -3t) = 2t + 6
(3t + -3t2) = 2t + 6

Reorder the terms:
3t + -3t2 = 6 + 2t

Solving
3t + -3t2 = 6 + 2t

Solving for variable 't'.

Reorder the terms:
-6 + 3t + -2t + -3t2 = 6 + 2t + -6 + -2t

Combine like terms: 3t + -2t = 1t
-6 + 1t + -3t2 = 6 + 2t + -6 + -2t

Reorder the terms:
-6 + 1t + -3t2 = 6 + -6 + 2t + -2t

Combine like terms: 6 + -6 = 0
-6 + 1t + -3t2 = 0 + 2t + -2t
-6 + 1t + -3t2 = 2t + -2t

Combine like terms: 2t + -2t = 0
-6 + 1t + -3t2 = 0

Begin completing the square.  Divide all terms by
-3 the coefficient of the squared term: 

Divide each side by '-3'.
2 + -0.3333333333t + t2 = 0

Move the constant term to the right:

Add '-2' to each side of the equation.
2 + -0.3333333333t + -2 + t2 = 0 + -2

Reorder the terms:
2 + -2 + -0.3333333333t + t2 = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -0.3333333333t + t2 = 0 + -2
-0.3333333333t + t2 = 0 + -2

Combine like terms: 0 + -2 = -2
-0.3333333333t + t2 = -2

The t term is -0.3333333333t.  Take half its coefficient (-0.1666666667).
Square it (0.02777777779) and add it to both sides.

Add '0.02777777779' to each side of the equation.
-0.3333333333t + 0.02777777779 + t2 = -2 + 0.02777777779

Reorder the terms:
0.02777777779 + -0.3333333333t + t2 = -2 + 0.02777777779

Combine like terms: -2 + 0.02777777779 = -1.97222222221
0.02777777779 + -0.3333333333t + t2 = -1.97222222221

Factor a perfect square on the left side:
(t + -0.1666666667)(t + -0.1666666667) = -1.97222222221

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 | | -9h+15=27-2h | | 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 | | 10x+8(x-3)-8= | | -6(x-1)-7=-7x+7 | | 10.8a+9.8a-7.9=-7.6 | | (x+6)((2x-1)(x+6))=0 | | (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x | | R^2-9/2r=29 | | 0=-16t^2+10t+56 | | -25+3x=0 | | 20n-19n+21=-21 | | x=4/3×3.14×7×7×7 | | 1/x^2-4=0 | | 15x-177=6x-6 | | 4x+4=3y+6 | | Log[9]5+log[9]4= | | 7.3=(2x)/(.3-x) | | X/5=x-7/7 | | 3/17x=-6 | | 15x^4+6x^2-18x^3= | | n/-1.8=2.1 |

Equations solver categories